1208 FEASIBILITY OF A PHARMACIST-LED INTERVENTION FOR ATRIAL FIBRILLATION IN LONG-TERM CARE: THE PIVOTALL STUDY. (16th January 2023) - Ritchie, L A; Penson, P E; Akpan, A; Lip, G Y H; Lane, D A
Abstract: Introduction: Older people in care homes with atrial fibrillation (AF) have complex health needs and would benefit from taking part in research. This study assessed the feasibility of pharmacist implementation of the Atrial Fibrillation Better Care (ABC: Anticoagulation; Better symptoms; Cardiovascular comorbidity management) pathway, and collection of an AF-specific, resident-centred outcome. Methods: Older residents (aged ≥65 years) with AF were recruited from care homes within Liverpool and Sefton and randomised to receive the pharmacist intervention, or continue their existing treatment. Resident quality of life was assessed using the Atrial Fibrillation Effect on Quality of Life Questionnaire (AFEQT). Results: Twenty-two care homes were approached about the study, and seven signed up to take part between 28 September 2020 and 29 April 2021. Time taken to recruit care homes ranged from 0 to 122 days. There were 83 residents identified as potentially eligible to take part, but after screening only 28 residents (34%) were invited. Overall, 21 residents were recruited. Eleven residents received the pharmacist intervention and three had ABC recommendations made to their GPs. Two out of four recommendations were implemented. The pharmacist administered the AFEQT questionnaire to 17 residents with capacity and completion rates were 94% and 93% at baseline and six-months, respectively. Residents found the questionnaire difficult; most were unable to distinguish if symptoms were AF-related (n=3), or did not know they had AF (n=8), and questions related to physical activity were not applicable to any of the residents who were bed bound (n=5) or had severely limited mobility (n=12). Conclusion: There were procedural (encountered before research starts), system (encountered during research) and resident-specific barriers that impacted this study. Barriers need addressing before wider implementation, and AF-specific quality of life measures need to be developed and validated for care home residents. A detailed commentary has been submitted for publication.